(untitled) (Asian Journal of Ethnobiology, 2022)
Abstract. Chandra S. 2022. Documentation of the plants used in different Hindu rituals in Uttarakhand, India. Asian J Ethnobiol 5: 92-101. Hinduism is one of the largest practicing religions. The Indian subcontinent is the cradle of this religion, and it is followed by a majority of the people of the subcontinent. Rituals are the main component of the Hindu tradition. Any ritual is a way to connect with God and offer salutation. From birth to the death of a person, one has to perform various rituals on enormous occasions. Methodology and material used in a ritual vary as per the presiding deity. In the sacrifice (Yajyan) and other worship procedures stage (Mandapa), different utensils and materials required to complete the rituals originated from plant products. These products represent the environmental and geographical structure of the area. Documentation of the plant species used in different Hindu rituals is done in the present article. A total of 104 plant species are enumerated. The use of plant species individually or in combination with others is also elaborated. Some terms used in the rituals, such as Panch Pallav, Panch Mewa, Saptanaja, Tambula, Panchamrita, Ashtha Bali, etc., which have botanical significance, are also discussed.